Association of β1- and β2-Adrenergic Receptor Gene Polymorphisms with the Effectiveness of Bisoprolol and Carvedilol in Patients with Heart Failure of Ischemic Etiology - Nadiia M. Kulaiets; Vira M. Kulaiets (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To study the relationship between β1-, β2-adrenergic receptor (β-AR) gene polymorphisms and the effectiveness of bisoprolol and carvedilol in patients with heart failure (HF) and coronary heart disease.Materials and methods. We examined 201 patients with HF on the background of post-infarction cardiosclerosis. Control group included 43 healthy individuals of comparable age and sex. Genotyping was carried out for 3 polymorphisms (rs1801253 and rs1801252 of the β1-AR gene; rs1042714 of the β2-AR gene). The patients were divided into 2 groups: the first group included 104 (51.7%) patients who took bisoprolol during the year of observation; 97 (48.3%) patients of the second group were treated with carvedilol. Statistical analysis was performed using Statistica 10.0 and SNPStats programs.Results. In patients with HF, the mutant C-allele (rs1801253 polymorphism) of the β1-AR gene was associated with a decrease in the probability of heart rate reduction >15 min-1 against the background of the use of β-blocker during the year (odds ratio [OR] = 0.42 [0.16-0.98], p = 0.041, recessive inheritance model; OR = 0.62 [0.40-0.97], p = 0.038; log-additive inheritance model). The probability of positive dynamics of the left ventricular ejection fraction (LVEF) increased in carriers of the wild A-allele of the rs1801252 (Ser49Gly) polymorphism of the β1-AR gene (OR = 4.86 [2.35-10.08], p < 0.0001, codominant model; OR = 5.18 [2.51-10.68], p < 0.0001, dominant model; OR = 4.68 [2.26-9.68], p < 0.0001, over-dominant model; OR = 5.05 [2.48-10.28], p < 0.0001, log-additive inheritance model). The probability of an increase in LVEF within a year increased with treatment with carvedilol in homozygous mutant G/G rs1042714 polymorphism (Gln27Glu) of the β2-AR gene in patients with HF (OR = 6.09 [1.16-31.88], p = 0.038, dominant inheritance model).Conclusions. Patients with HF of ischemic etiology, carriers of the mutant C-allele of rs1801253 polymorphism of the β1-adrenoceptor gene, are worse responders to the use of β-blockers compared to patients with the wild G-allele (a lower proportion of patients with a decrease in heart rate >15 min-1: 6.8% vs. 14.5%, respectively; OR = 0.42 [0.16-0.98], p = 0.041). The frequency of an increase in the value of the LVEF >10% was higher compared to patients with the mutant G-allele (39.3% vs. 11.1%, respectively; OR = 4.86 [2.35-10.08], p < 0.0001) against the background of application of β-blockers. The use of carvedilol was more appropriate in homozygous carriers of the mutant G-allele of the rs1042714 polymorphism (Gln27Glu) of the β2-AR gene compared to bisoprolol (a greater proportion of patients with an increase in the LVEF: 17.6% vs. 9.1%, respectively; OR = 6.09 [1.16-31.88], p = 0.038). No probable associations of rs1801253 and rs1801252 polymorphisms of the β1-AR gene with the pharmacodynamics of bisoprolol and carvedilol in patients with HF of ischemic etiology were found.